2006
DOI: 10.1080/03069880600769118
|View full text |Cite
|
Sign up to set email alerts
|

Women, careers, and work-life preferences

Abstract: There are no sex differences in cognitive ability but enduring sex differences in competitiveness, life goals, the relative emphasis on agency versus connection. Policy-makers' and feminist emphasis on equal opportunities and family-friendly policies assumes that sex discrimination is the primary source of sex differentials in labour market outcomes *notably the pay gap between men and women. However, some careers and occupations cannot be domesticated *examples are given *and this also poses limits to social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
320
1
41

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(370 citation statements)
references
References 24 publications
(18 reference statements)
8
320
1
41
Order By: Relevance
“…In contrast, women tend to be more motivated by affiliation-the desire for warm, close relationships with others (32). Reinforcing this point, in studies using samples of talented individuals, the life values and personal views of men and women have been found to differ (33), with men tending to assume a more agentic, career-focused perspective, whereas women generally favor a more communal, holistic perspective (34)(35)(36). These differing views seem to cause differences in how men and women allocate their time and attention (33).…”
Section: Significancementioning
confidence: 88%
“…In contrast, women tend to be more motivated by affiliation-the desire for warm, close relationships with others (32). Reinforcing this point, in studies using samples of talented individuals, the life values and personal views of men and women have been found to differ (33), with men tending to assume a more agentic, career-focused perspective, whereas women generally favor a more communal, holistic perspective (34)(35)(36). These differing views seem to cause differences in how men and women allocate their time and attention (33).…”
Section: Significancementioning
confidence: 88%
“…Whether the direct effects of biological sex on the brain, and hence on motivation/interests/activities and abilities, are a major contribution to the dearth of women in math-intensive fields, however, is unclear, hence, the paleness of the arrows marking these pathways. For example, if women are more home-centered and innately more interested in raising children (Hakim, 2006), then biological sex feeds directly into brain development/ functioning and hence into motivation/interests/activities, which in turn affect career status through life choices ( Figure A3 in the supplemental materials). It is possible, however, that any direct biological impact is small, with the bulk of the gender-interests relationship indirect, mediated by factors such as cultural expectations ( Figure A3 in the supplemental materials).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Available evidence points to a special fertility penalty for mothers of young children in getting promoted in some math-intensive fields (e.g., Ginther & Kahn, 2006, reported that women were 9.6% less likely than comparable men to get promoted to full professor in the physical sciences). Encouragingly, the "childbearing penalty" is probably the most malleable of the factors we considered: If society deemed it desirable to increase the representation of women, various strategies could be implemented (see Shalala et al, 2007), such as deferred start-up of tenure-track positions and part-time work that segues to full-time tenure track work when children are no longer in need of intensive care, designed flexibly to keep these women from opting out entirely, although one cannot assume that such changes will have the desired result if women disproportionately prefer home-centered and adaptive work lifestyles rather than single-minded commitment to career lifestyles (Hakim, 2006(Hakim, , 2007. Moreover, the viability of such a policy may vary from field to field, corresponding to the rate of knowledge obsolescence.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…From social role theory (Eagly, 1997) to circumscription and compromise (Gottfredson, 1981) to preference theory (Hakim, 2006) to tokenism (Kanter, 1977) to educational tracking (Ainsworth & Roscigno, 2005;Eardley & Manvell, 2006), there are no shortages of premises offered to explicate the problem and propose solutions. Although scholars remain divided on the cause, there is little dispute that gender segregation in the workforce is a genuine concern that warrants a resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not men and women select careers based upon internal preferences (Evans & Diekman, 2009;Hakim, 2006) or if their choices are a byproduct of early gender socialization (Bussey & Bandura, 1999;Tobin et al, 2010) remains a healthy debate amongst scholars. Historically, early studies of gender were primarily concerned with understanding the differentiating behaviors and belief systems that separated males and females.…”
Section: Introductionmentioning
confidence: 99%